Effect of Global ATGL Knockout on Murine Fasting Glucose Kinetics. (5th July 2015) - Coelho, Margarida; Nunes, Patricia; Mendes, Vera M.; Manadas, Bruno; Heerschap, Arend; Jones, John G.
Abstract : Mice deficient in adipose triglyceride lipase (ATGL −/− ) present elevated ectopic lipid levels but are paradoxically glucose-tolerant. Measurement of endogenous glucose production (EGP) and Cori cycle activity provide insights into the maintenance of glycemic control in these animals. These parameters were determined in 7 wild-type (ATGL +/− ) and 6 ATGL −/− mice by a primed-infusion of [U- 13 C6 ]glucose followed by LC-MS/MS targeted mass-isotopomer analysis of blood glucose. EGP was quantified by isotope dilution of [U- 13 C6 ]glucose while Cori cycling was estimated by analysis of glucose triose 13 C-isotopomers. Fasting plasma free fatty-acids were significantly lower in ATGL −/− versus control mice (0.43 ± 0.05 mM versus 0.73 ± 0.11 mM, P < 0.05 ). Six-hour fasting EGP rates were identical for both ATGL −/− and control mice (79 ± 11 versus 71 ± 7  μ mol/kg/min, resp.). Peripheral glucose metabolism was dominated by Cori cycling (80 ± 2% and 82 ± 7% of glucose disposal for ATGL −/− and control mice, resp.) indicating that peripheral glucose oxidation was not significantly upregulated in ATGL −/− mice under these conditions. The glucose 13 C-isotopomer distributions in both ATGL −/− and control mice were consistent with extensive hepatic pyruvate recycling. This suggests that gluconeogenic outflow from the Krebs cycle was also well compensated in ATGL −/− mice.